Carbon dioxide (CO₂) absorption in blends of aqueous solutions of monoethanolamine (MEA) and L-serine / Mishalny Nair Raghavan - Mishalny Nair, Raghavan (2022)
Expansion in carbon dioxide discharges in the climate is a widespread matter that needs a conclusive determination in order to direct the creating hazard of environment change. Various examinations have been led over the end to settle this issue. The principal investigation of this study is to investigate the solubility of CO2 in aqueous MEA + L-Ser solution. This is done by exploring the effect of various elements on the absorption process, for example, concentration, temperature and CO2 loading. In this work, CO2 solubility is estimated in the aqueous solution of monoethanolamine (MEA) + Serine (L-Ser) using a high-pressure CO2 absorption reactor. The analysis was done at various pressure (50–200 psi) and under four distinct temperatures (303.15 K–333.15 K). The composition of aqueous solutions was used as 2.0 M MEA, 1.5 M MEA + 0.5 M L-SER and 1.0 M MEA + 1.0 M L-SER. It was seen that at a similar pressure; the CO2 loading decreases with an increase in temperature. For sure, at a consistent temperature, the solution loading increases as the pressure builds, which shows that the response is exothermic response. It is prescribed to investigate more on the solubility of CO2 absorption using original form of amino acids with various solvents like MDEA, DEA, DIPA and so forth.